Pengaruh kepemimpinan transformasional terhadap pengembangan sumber daya manusia di sebuah satuan pendidikan - Variani, Herlin; Qadri, Hanif Al; Nellitawati, Nellitawati (Academy of Education Journal, 2024)
This research aims to explore the influence of transformational leadership on the development of human resources (HR) in an educational unit. The research method used is a library research approach or literature study, with analysis of relevant literature on transformational leadership and human resource development in the education sector. The research results show that transformational leadership has a positive impact on human resource development in an educational unit. Through high motivation, skill development, increased collaboration and creativity, improved performance, and continuous leadership development, transformational leadership creates an environment that supports individual growth and achievement of organizational goals. However, the implementation of transformational leadership is also faced with challenges and obstacles, such as changes in organizational culture, lack of support from related parties, limited resources, difficulties in measurement and evaluation, unsupportive policies and regulations, lack of leader skills and knowledge, resistance from interest groups. particular, and dependence on individual leaders. In conclusion, transformational leadership has great potential to influence human resource development in an educational unit, but needs to be faced with various challenges and obstacles in its implementation.